Experimental study on the lateral thrust generated by core buckling in bolted-BRBs. (July 2016) - Metelli, Giovanni; Bregoli, Guido; Genna, Francesco
Abstract: The paper presents the results of cyclic loading tests on all-steel buckling-restrained braces (BRBs), with the aim of investigating the contact phenomena and the associated lateral thrust occurring when the inner core of a BRB, after buckling, comes into contact with the external restraining case. A special test set-up was employed to detect the shape and extension of the contact zones, as well as the local contact pressures. Attention was focused on the role of certain key parameters governing the high-mode plastic buckling of the core, such as the size of the gap between the core and the restraining members, the stiffness of the containing case, and the cyclic loading history. The results show that the value of the lateral thrust generated by the core during its high-mode buckling increases, possibly up to very high values, with the gap/core thickness ratio, the axial core strain, and the cumulated plastic deformation of the core. The results might be a useful tool both to validate analytical expressions and numerical models for the assessment of the lateral thrust. Moreover, test results on full-size all-steel bolted BRBs showed that the design of the containment profiles and relevant connections cannot be made without an accurate estimate of the lateral thrust exerted by the buckled core under the adopted loading conditions. Highlights: Tests on all steel bolted BRBs are presented. The outward thrust exerted by the core against the case was measured. Sensors recorded dynamically the shape of the core elastic-plastic buckled waves. The thrust depends on gap size, axial strain and on the shape of the buckled wave. The results are an effective tool to validate analytical and numerical models.